2017
DOI: 10.1177/2325967117711376
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Its Effects on Articular Cartilage and Osteoarthritis

Abstract: Background:Osteoarthritis (OA) currently affects 10% of the American population. There has been a recent push to determine exactly what causes OA and how it can be treated most effectively. Serum vitamin D levels have been associated with OA and may have an effect on articular cartilage remodeling.Purpose:To critically review the published research on the effect of vitamin D on articular cartilage and the development of OA as well as on the mechanism behind cartilage regeneration and degeneration.Study Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 52 publications
0
41
0
3
Order By: Relevance
“…Osteoarthritis is a disease of the synovial membrane, subchondral bone and cartilage, and the low intake and low levels of vitamin D in the blood can exacerbate osteoarthritis and cause the disease to develop [50]. In a study, the results showed that the risk of osteoarthritis had increased three times in participants in the lower and middle groups of vitamin D levels in the blood and it was concluded that low levels of vitamin D in the blood increase the risk of bone arthritis [51,52].…”
Section: Vitamin D and Bone Healthmentioning
confidence: 99%
“…Osteoarthritis is a disease of the synovial membrane, subchondral bone and cartilage, and the low intake and low levels of vitamin D in the blood can exacerbate osteoarthritis and cause the disease to develop [50]. In a study, the results showed that the risk of osteoarthritis had increased three times in participants in the lower and middle groups of vitamin D levels in the blood and it was concluded that low levels of vitamin D in the blood increase the risk of bone arthritis [51,52].…”
Section: Vitamin D and Bone Healthmentioning
confidence: 99%
“…Emerging observational data suggest that vitamin D insufficiency is associated with the onset and progression of knee OA. 7 The association between low serum vitamin D levels and knee OA symptoms may be explained by a direct effect of vitamin D on chondrocytes in osteoarthritic cartilage, 8 as well as indirect effects on subchondral bone, synovium and periarticular muscle. 9 For example, vitamin D deficiency could impair the ability of bone to respond optimally to pathological bone marrow lesions (BMLs) and altered bone mineral density, therefore predisposing the knees to disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…These observations are likely related to the changes in subchondral bone seen in both mouse and human OA(27). Increased vitamin D signaling has previously been reported in arthritic joints in response to joint damage to induce new bone formation, with this increased bone remodeling associated with joint pain(28, 29). In this noninvasive injury model, we observe dramatic bone remodeling as early as 3 days postinjury, resulting in a 25-35% loss of subchondral bone volume peaking at 7-10 days post-injury(30).…”
Section: Discussionmentioning
confidence: 91%